Early-onset parkinsonism in a pedigree with phosphoglycerate kinase deficiency and a heterozygous carrier: do PGK-1 mutations contribute to vulnerability to parkinsonism? - Satoshi Sakaue (Nature Portfolio, 2017)
Early-onset Parkinson’s disease: a new genetic link Mutations in the gene encoding phosphoglycerate kinase 1 (PGK-1) may confer susceptibility to early-onset Parkinson’s disease (PD). PGK-1 is a crucial protein for the breakdown of sugar in the body and mutations that cause PGK-1 deficiency lead to an X-linked metabolic disorder characterised by the breakdown of red blood cells, muscle weakness and various central nervous system abnormalities. Takashi Kasai at Kyoto Prefectural University of Medicine, Japan, and colleagues describe early-onset PD symptoms in a 9 year old boy with PGK-1 deficiency and his mother at 36 years of age. This is the first report of parkinsonism developing in an otherwise asymptomatic carrier of a PGK-1 mutation. The location of the PGK-1 gene on the X chromosome is within a confirmed susceptibility region for PD known as PARK12, suggesting that PGK-1 may directly contribute to the disease.